Differential bioaccumulation and translocation patterns in three mangrove plants experimentally exposed to iron. Consequences for environmental sensing - Arrivabene, Hiulana Pereira [UNESP]; Campos, Caroline Quenupe; Souza, Iara Da Costa; Wunderlin, Daniel Alberto; Milanez, Camilla Rozindo Dias; Machado, Silvia Rodrigues [UNESP] (Elsevier, 2016)
Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle were experimentally exposed to increasing levels of iron (0, 10, 20 and 100 mg L-1 added Fe(II) in Hoagland's nutritive medium). The uptake and translocation of iron from roots to stems and leaves, Fe-secretion through salt glands (Avicennia schaueriana and Laguncularia racemosa) as well as anatomical and histochemical changes in plant tissues were evaluated. The main goal of this work was to assess the diverse capacity of these plants to detect mangroves at risk in an area affected by iron pollution (Vitoria, Espírito Santo, Brazil). Results show that plants have differential patterns with respect to bioaccumulation, translocation and secretion of iron through salt glands. L. racemosa showed the best environmental sensing capacity since the bioaccumulation of iron in both Fe-plaque and roots was higher and increased as the amount of added-iron rose. Fewer changes in translocation factors throughout increasing added-iron were observed in this species. Furthermore, the amount of iron secreted through salt glands of L. racemosa was strongly inhibited when exposed to added-iron. Among three studied species, A. schaueriana showed the highest levels of iron in stems and leaves. On the other hand, Rhizophora mangle presented low values of iron in these compartments. Even so, there was a significant drop in the translocation factor between aerial parts with respect to roots, since the bioaccumulation in plaque and roots of R. mangle increased as iron concentration rose. Moreover, rhizophores of R. mangle did not show changes in bioaccumulation throughout the studied concentrations. So far, we propose L. racemosa as the best species for monitoring iron pollution in affected mangroves areas. To our knowledge, this is the first detailed report on the response of these plants to increasing iron concentration under controlled conditions, complementing existing data on the behavior of the same plants under field exposure.
Keywords: Histochemistry; Iron bioaccumulation; Iron plaque; Iron translocation; Mangrove pollution; Pollution sensing